On a subclass of goodman-ronning type harmonic univalent functions defined by Dziok-Srivastava operator - Akrabally, Ajab; Hassan, Suraya (HIKARI Ltd., 2016)
The aim of this paper is to investigate a subclass of Goodman-Ronning type of harmonic univalent functions defined by the modified Dziok-Srivastava operator. The properties for this class such as the coefficient conditions, distortions bounds and extreme points are investigated.